2013
DOI: 10.1128/jvi.03316-12
|View full text |Cite|
|
Sign up to set email alerts
|

The Lack of Maturation of Ebola Virus-Infected Dendritic Cells Results from the Cooperative Effect of at Least Two Viral Domains

Abstract: dEbola virus (EBOV) infections are characterized by deficient T lymphocyte responses, T lymphocyte apoptosis, and lymphopenia in the absence of direct infection of T lymphocytes. In contrast, dendritic cells (DC) are infected but fail to mature appropriately, thereby impairing the T cell response. We investigated the contributions of EBOV proteins in modulating DC maturation by generating recombinant viruses expressing enhanced green fluorescent protein and carrying mutations affecting several potentially immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
127
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(138 citation statements)
references
References 80 publications
10
127
0
Order By: Relevance
“…We found that the EBOV VP35 and VP24 cooperatively suppress maturation of infected human DC and that the mutations R312A in VP35 and, to a lesser degree, K142A in VP24 reverse this inhibition of maturation (15).…”
mentioning
confidence: 86%
See 3 more Smart Citations
“…We found that the EBOV VP35 and VP24 cooperatively suppress maturation of infected human DC and that the mutations R312A in VP35 and, to a lesser degree, K142A in VP24 reverse this inhibition of maturation (15).…”
mentioning
confidence: 86%
“…To make the recombinant EBOV carrying both the mutation R312A in VP35 and the mutation K142A in VP24 and expressing the enhanced green fluorescent protein (eGFP) gene, we used the previously constructed plasmid pEBOV-eGFP/VP35-R312A carrying the mutation in VP35 and pEBOVeGFP/VP24-K142A with the mutation in VP24 and each expressing the eGFP gene inserted between the NP and VP35 genes (15). The SalI-SacI fragment of the full-length pEBOV-eGFP/VP35-R312A plasmid, including part of the GP gene, the VP30 gene, and part of the VP24 gene, was replaced with its mutagenized copy from pEBOV-eGFP/VP24-K142A plasmid.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite lack of disparity assessment of VP24 and VP35, 2 ebola virus' suppression of the maturation of dendritic cells of immune system with several viral proteins in co-operation (e.g., GP, VP24 and VP35) results in escaping the detection and response of host immune system. 27 Recently, for VP35, Leung et al 28 have concluded that the major determinant of their functional di®erences is not likely the conformational variations observed in the VP35 C-terminal basic domains between Reston and Zaire viruses, due to limited tolerance for amino acid variations in this domain. As for VP30, homodimers of VP30 have been observed for both Reston and Zaire viruses, and the residue sequences of both dimerization domains of VP30 are highly conserved, suggesting resistance of this dimerization domain to functionally signi¯cant variations.…”
mentioning
confidence: 99%